2021
DOI: 10.3390/ijerph18137041
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Admissions Due to Ischemic Heart Diseases and Prescriptions of Cardiovascular Diseases Medications in England and Wales in the Past Two Decades

Abstract: Objectives: The aim of this study was to explore the trend of ischemic heart disease (IHD) admission and the prescriptions of IHD medications in England and Wales. Methods: A secular trends study was conducted during the period of 1999 to 2019. We extracted hospital admission data for patients from all age groups from the Hospital Episode Statistics database in England and the Patient Episode Database for Wales. Prescriptions of IHD medications were extracted from the Prescription Cost Analysis database from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Previous studies in Denmark, Sweden, and Norway explored the utilisation pattern of different classes of medications such as opioids and antiarrhythmic medications and reported an increase in their utilisation [ 33 35 ]. Recent studies in the UK showed an increase in hospitalizations for various acute and chronic conditions, such as viral diseases, respiratory diseases, and heart diseases [ 19 , 36 , 37 ]. Raised hospitalisation rates highlight that there is an increase in the prevalence of these diseases that lead to hospitalisation, which itself could lead to an increase in the prescribing pattern of medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in Denmark, Sweden, and Norway explored the utilisation pattern of different classes of medications such as opioids and antiarrhythmic medications and reported an increase in their utilisation [ 33 35 ]. Recent studies in the UK showed an increase in hospitalizations for various acute and chronic conditions, such as viral diseases, respiratory diseases, and heart diseases [ 19 , 36 , 37 ]. Raised hospitalisation rates highlight that there is an increase in the prevalence of these diseases that lead to hospitalisation, which itself could lead to an increase in the prescribing pattern of medications.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Hemmo et al has explored the hospitalisation pattern for ischemic heart diseases (IHD)s and the prescription pattern for CVD medication for the period between 1999 and 2019 [ 19 ]. Their study found that the prescription rate for beta-blockers, calcium channel blockers, anti-platelets, and lipid-lowering medications, was negatively correlated with IHD-related hospital admission rates [ 19 ]. The prescription rate for these medications increased as they are mainly maintenance therapy and have been shown to improve symptoms and prolong survival [ 46 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was an ecological study using publicly available data extracted from the Hospital Episode Statistics (HES) database in England [16] and the Patient Episode Database for Wales (PEDW) for the period between April 1999 and April 2019 [17]. They have been used previously to explore the trends of different health outcomes and the associated hospital admissions [18][19][20][21]. The hospital episode statistics database and patient episode database for Wales record all hospital admissions, outpatients and accident and emergency (A&E) activities performed at all NHS trusts and any independent sector funded by NHS trusts.…”
Section: Study Sources and Populationmentioning
confidence: 99%
“…This was an ecological study using data extracted from the Hospital Episode Statistics (HES) database in England [ 17 ] and the Patient Episode Database for Wales (PEDW) for the period between April 1999 and April 2019 [ 18 ]. They have been used previously to explore the trends of different health outcomes and the associated hospital admissions [ 19 , 20 ]. The HES and PEDW databases contain hospital admission data for patients with viral infections characterized by skin and mucous membrane lesions from all age groups, which are subdivided into four categories; below 15 years, 15–59 years, 60–74 years, and 75 years and above.…”
Section: Methodsmentioning
confidence: 99%